Життя як школа, а ти в ній вічний учень - Андрушків, Б.М. (Вісник економічної науки України, 2022)
У статті розкрито особливості формування, досягнення і втрати наукової школи Богдана Андрушківа: «Регіональні і міжрегіональні аспекти підтримки соціально-економічної реформи, інноваційні контексти розвитку підприємництва на сучасному етапі» за 20-ти річний період. Інформаційний матеріал підготовлено на досвіді управління економічною кафедрою у Тернопільському національному технічному університеті ім. Івана Пулюя.
Дослідження розкриває витоки виникнення наукових шкіл ТНТУ, їх поетапний розвиток у контексті становлення економічної кафедри в умовах технічного закладу вищої освіти. Висвітлено досвід формування в умовах «безгрошів¢я» дослідницьких лабораторій, матеріально-технічної та навчально-методичної баз кафедри. Складнощі підготовки не лише студентів – бакалаврів, спеціалістів і магістрів, які передбачають присвятити себе у майбутньому підприємництву, розвитку сфери послуг та інноваційній діяльності, а і наукових кадрів вищої кваліфікації. Розглянуто організацію науково-дослідницької роботи, видавничої діяльності та виховання майбутнього покоління держави, дано пропозиції і рекомендації з їх розвитку у повоєнних умовах.
У статті повідомляється, що у перспективі автором готується видання з теми функціонування наукових шкіл під. Книга буде присвячена 150- річчю НТШ, 20-річчю кафедри управління інноваційною діяльністю та сферою послуг ТНТУ імені Івана Пулюя та 60-річчю університету. The article reveals the peculiarities of the formation, achievements and loss of the scientific school of Bohdan Andrushkiv: "Regional and interregional aspects of supporting socio-economic reform, innovative contexts of entrepreneurship development at the current stage" over a 20-year period. The informational material was prepared based on the experience of managing the Department of Economics at the Ternopil National Technical University named after Ivan Puliui.
The study reveals the origins of the scientific schools of TNTU, their gradual development in the context of the formation of the economic department in the conditions of a technical institution of higher education. The experience of forming research laboratories, material-technical and educational-methodical bases of the department in the conditions of "free money" is highlighted. The difficulties of training not only students - bachelors, specialists and masters, who intend to devote themselves in the future to entrepreneurship, development of the service sector and innovative activities, but also highly qualified scientific personnel. The organization of scientific and research work, publishing activities and education of the future generation of the state is considered, proposals and recommendations for their development in post-war conditions are given.
The article informs that in the future the author is preparing a publication on the topic of the functioning of scientific schools under The book will be dedicated to the 150th anniversary of the National Technical University, the 20th anniversary of the department of innovative activity management and the sphere of services of the Ivan Puliui State Technical University, and the 60th anniversary of the university.